2018
DOI: 10.1186/s12933-018-0772-2
|View full text |Cite
|
Sign up to set email alerts
|

Both pre-frailty and frailty increase healthcare utilization and adverse health outcomes in patients with type 2 diabetes mellitus

Abstract: BackgroundDiabetes mellitus (DM) correlates with accelerated aging and earlier appearance of geriatric phenotypes, including frailty. However, whether pre-frailty or frailty predicts greater healthcare utilization in diabetes patients is unclear.MethodsFrom the Longitudinal Cohort of Diabetes Patients in Taiwan (n = 840,000) between 2004 and 2010, we identified 560,795 patients with incident type 2 DM, categorized into patients without frailty, or with 1, 2 (pre-frail) and ≥ 3 frailty components, based on FRAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
101
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 55 publications
(65 reference statements)
0
101
1
Order By: Relevance
“…More generally, frailty, regardless of how it is defined, is associated with incident falls, difficulty with activities of daily living, disability, hospitalisation and death 24. While T2DM itself is associated with an elevated risk of mortality and healthcare utilisation, frailty magnifies these risks 25. It is important to determine if there is an interaction between parameters of sleep, T2DM and individual components of frailty.…”
Section: Introductionmentioning
confidence: 99%
“…More generally, frailty, regardless of how it is defined, is associated with incident falls, difficulty with activities of daily living, disability, hospitalisation and death 24. While T2DM itself is associated with an elevated risk of mortality and healthcare utilisation, frailty magnifies these risks 25. It is important to determine if there is an interaction between parameters of sleep, T2DM and individual components of frailty.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies on the effect of vitamin D on pre-frailty and frailty in ESRD patients and even those with other metabolic disorders are needed. 43,44 In this study, we found that those with high LFI-1 scores had a significantly higher mortality than those with low scores, but not for LFI-2. Several reasons may be responsible for this discrepancy in outcome predictability.…”
Section: Discussionmentioning
confidence: 47%
“…Serum 1,25‐(OH) 2 ‐D levels may be associated not only with frail phenotype but also with FI in elderly and in ESRD patients alike. Further studies on the effect of vitamin D on pre‐frailty and frailty in ESRD patients and even those with other metabolic disorders are needed …”
Section: Discussionmentioning
confidence: 99%
“…We selected patients with DM from the Longitudinal Cohort of Diabetes Patients (LCDP), a well-maintained cohort of patients with diabetes derived from an annual random selection of 120 000 patients with at least one diagnosis of diabetes from the National Health Insurance Database in Taiwan, between 2004 and 2010 7 8. This led to an initial cohort size of 840 000 during the study period.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with DM are at a higher risk of exhibiting frailty, a degenerative trait characterized by a higher vulnerability to endogenous or environmental injuries, regardless of their age, likely due to the combinatorial effects of hyperglycemia-induced premature cellular senescence, chronic inflammation, and oxidative stress 6. Accumulating evidence indicates that frailty in patients with diabetes causes adverse outcomes ranging from effects on mortality and functional independence, to musculoskeletal degeneration, an increased risk of cardiovascular events, and renal failure 7 8. None of the existing studies has examined whether frailty may influence the probability of urolithiasis in patients with DM.…”
Section: Introductionmentioning
confidence: 99%